A NEW QUANTITATIVE ANALYTICAL METHOD DEVELOPMENT AND VALIDATION FOR THE ANALYSIS OF BOCEPREVIR IN BULK AND MARKETED FORMULATION (International Journal of Pharmaceutical Sciences and Drug Research, 2018)
A simple, precise and accurate RP-HPLC technique was developed and the developed method was validated for the regular analysis of Boceprevir. Chromatographic analysis was performed by selecting X-Terra ODS ( C18) column (4.6 mm i.d. × 250 mm, 5μ), Acetonitrile : Phosphate buffer pH -3 ( 90 : 10% v/v) as mobile phase, 1.0 ml/min as flow rate and 20μl injection volume. The LC chromatographic peak was eluted at 3.6 min at 235 nm as UV detection wavelength. The developed method was validated as per the ICH guidelines and the Validation parameters were specificity, accuracy, linearity, precision, LOD and LOQ. Linear relationship for Boceprevir established in the concentration range of 50 to 150μg/mL. Accuracy in terms of percentage recovery found in the range between 98 to 101%. LOD and LOQ values were found to be 2.3 and 7.123μg/mL respectively. The results of the method established that the new RP-HPLC method is convenient and simple in regular analysis of Boceprevir in bulk and capsule formulation.